Pengaruh Terorisme, Investasi, Dan Pengeluaran Pemerintah Terhadap Pertumbuhan Ekonomi Di Indonesia Periode 2014-2023 - Bela Ika Saputri; Ika Wahyuningsih; Rangga Restu Prayoga; Muhammad Kurniawan (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
Indonesia is one of the countries with the 3rd highest economic growth rate in the ASEAN region. Economic growth in Indonesia has experienced fluctuations from year to year 2014-2023, Indonesia has stated stable economic growth ranging between 4-6% per year. Stable economic growth in Indonesia has a significant impact on various aspects, including terrorism, investment and government spending. Terrorist attacks can cause major economic losses for a country. This decline was caused by uncertainty caused by the loss of investors. Terrorist attacks can impact government spending because governments must allocate additional resources for security, law enforcement, and post-attack recovery. This expenditure includes improving national security, increasing police and security forces, as well as assistance to victims and restoration of damaged infrastructure. TR, INV and PP together have a positive but insignificant effect on economic growth.